Embedding Social Justice within Micro Social Work Curricula. (2nd July 2016) - Harrison, Jennifer; VanDeusen, Karen; Way, Ineke
ABSTRACT: Social work struggles with the dichotomy between social and economic justice and micro practice. A large percentage of United States social workers (65%) practice in micro practice settings, yet the profession is challenged to commit to its social justice roots. This article reviews the history of social and economic justice within the social work profession, examines the role of distributive justice, and outlines strategies to integrate social and economic justice into micro social work courses. The article details implications for strengthening a social and economic justice perspective in micro curricula.